2020
DOI: 10.1093/nar/gkaa561
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient ‘hit-and-run’ genome editing with unconcentrated lentivectors carrying Vpr.Prot.Cas9 protein produced from RRE-containing transcripts

Abstract: Abstract The application of gene-editing technology is currently limited by the lack of safe and efficient methods to deliver RNA-guided endonucleases to target cells. We engineered lentivirus-based nanoparticles to co-package the U6-sgRNA template and the CRISPR-associated protein 9 (Cas9) fused with a virion-targeted protein Vpr (Vpr.Prot.Cas9), for simultaneous delivery to cells. Equal spatiotemporal control of the vpr.prot.cas9 and gag/pol gene expression (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
0
33
0
3
Order By: Relevance
“…The results from our study highlight the potential therapeutic benefit of using rational engineering to further advance delivery platforms for gene editing agents. While VLPs have been used previously to deliver Cas9 nuclease RNPs (Campbell et al, 2019;Choi et al, 2016;Gee et al, 2020;Hamilton et al, 2021;Indikova and Indik, 2020;Lyu et al, 2019;Mangeot et al, 2019), and a recent study used VLPs to deliver BE RNPs to HEK293T cells with lower efficiencies than the eVLPs described here (Lyu et al, 2021), no previous study to our knowledge has reported therapeutic levels of postnatal in vivo gene editing of any type using RNP-delivering VLPs. The eVLP platform developed in this work uses a rationally engineered architecture that we customized to package increased amounts of cargo and improve particle titers.…”
Section: Discussionmentioning
confidence: 96%
“…The results from our study highlight the potential therapeutic benefit of using rational engineering to further advance delivery platforms for gene editing agents. While VLPs have been used previously to deliver Cas9 nuclease RNPs (Campbell et al, 2019;Choi et al, 2016;Gee et al, 2020;Hamilton et al, 2021;Indikova and Indik, 2020;Lyu et al, 2019;Mangeot et al, 2019), and a recent study used VLPs to deliver BE RNPs to HEK293T cells with lower efficiencies than the eVLPs described here (Lyu et al, 2021), no previous study to our knowledge has reported therapeutic levels of postnatal in vivo gene editing of any type using RNP-delivering VLPs. The eVLP platform developed in this work uses a rationally engineered architecture that we customized to package increased amounts of cargo and improve particle titers.…”
Section: Discussionmentioning
confidence: 96%
“…Using chemical induced dimerization Cas9 protein and the gRNAs encoding construct carrying a viral packaging signal both were incorporated into these nanovesicles. Indikova and Indik ( 2020 ) engineered lentivirus-based nanoparticles to co-package the U6-sgRNA template and the CRISPR/Cas9 fused with a virion-targeted protein Vpr (Vpr.Prot.Cas9), for simultaneous delivery to cells. The three systems were highly efficient for gene editing in cell lines and some in primary cells such as induced pluripotent stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…This protein fusion orientation allowed guide RNA to associate with fused Cas9 within the MLV VLPs, thereby allowing for the delivery of pre-formed Cas9 RNP complexes capable of mediating robust levels of genome editing in target cells. Recently it has been demonstrated that fusing Cas9 to the lentiviral accessory protein Vpr also promotes Cas9 packaging in budding particles ( Indikova and Indik, 2020 ). Vpr-Cas9-containing lentivirus was highly effective at mediating genome editing in immortalized cell lines but only modestly effective (2.7%–15% indels) at mediating genome editing in primary human CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%